PERUBAHAN NON-FORMAL KONSTITUSI DI INDONESIA PASCA-REFORMASI BERDASARKAN PEMIKIRAN FAJRUL FALAAKH - Aldiansyah, Aldiansyah (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2021)
The constituent changes in Post-Reformation Indonesia are very interesting to discuss ranging from formal amendment changes and non-formal changes that change without changing the text of the constitution in question. Also happens informally (informal change informal amendment), namely changes to the contituents without changing the text of the contitution concerned or changes outside the text of the contitutionâ€. Formal amendments (formal changes) are only one way to change the constitution. Changes can also occur non-formally (informal changes, informal amendments), namely changes to the constitution without changing the text in question or changes